2016
DOI: 10.1080/21548455.2016.1254358
|View full text |Cite
|
Sign up to set email alerts
|

Making the invisible observable by Augmented Reality in informal science education context

Abstract: The aim of the study was to analyse learning using Augmented Reality (AR) technology and the motivational and cognitive aspects related to it in an informal learning context. The 146 participants were 11-to 13-year-old Finnish pupils visiting a science centre exhibition. The data, which consisted of both cognitive tasks and self-report questionnaires, were collected using a pre-post-test design and were analysed by SEM pathanalysis. The results showed that AR-technology experience was beneficial for all, but e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 30 publications
6
33
0
2
Order By: Relevance
“…His criticism of the passive pedagogy of science education derives implicitly from Dewey's ideas (1938) expressed in his thesis of 'learning by doing'. The same approach can be seen in contemporary developments in science centre pedagogy (Braund and Reiss 2004;Salmi 1993Salmi , 2003Salmi et al 2017): The famous 'hands-on' principle articulated by Oppenheimer is a cornerstone of the interaction in modern science centres. What Dewey and modern science centre pedagogy share is the emphasis on motivation, free will and the learner's own activity which is stimulated by the context and is not forced.…”
Section: Informal Science Learning In Open Learning Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…His criticism of the passive pedagogy of science education derives implicitly from Dewey's ideas (1938) expressed in his thesis of 'learning by doing'. The same approach can be seen in contemporary developments in science centre pedagogy (Braund and Reiss 2004;Salmi 1993Salmi , 2003Salmi et al 2017): The famous 'hands-on' principle articulated by Oppenheimer is a cornerstone of the interaction in modern science centres. What Dewey and modern science centre pedagogy share is the emphasis on motivation, free will and the learner's own activity which is stimulated by the context and is not forced.…”
Section: Informal Science Learning In Open Learning Environmentsmentioning
confidence: 99%
“…The role of informal learning is increasing with the growing impact of new technologies (Radu 2014), digitalisation and research results related to our everyday lives. Lifelong learning in modern societies needs new practical forms , and thus, informal education has become a widely accepted and integrated part of school systems during the last three decades (Fenichel and Schweingruber 2010;Salmi 1993;Salmi et al 2017). Out-of-school education forms a pedagogical link between formal education and informal learning (Braund and Reiss 2007;Rennie et al 2003) because it is a term included in school legislation in several countries (Rennie 2014).…”
Section: Informal Science Learning In Open Learning Environmentsmentioning
confidence: 99%
“…However, these results contradict the earlier reports in the literature [cf. [62]], which indicates that the high achievers benefit from the informal learning settings like science center exhibitions most of all.…”
Section: Discussionmentioning
confidence: 99%
“…They used AR-based motion-sensing software and results showed that it could increase their learning and attitude. Salmi et al [57] investigated motivational and cognitive aspects of informal learning while using AR technology in learning process and made a SEM path analysis. They focused on science education and found that AR was effective especially in lowest achieving group and for girls.…”
Section: Using Augmented Reality In Secondary Educationmentioning
confidence: 99%